Aggressive Angiomyxoma of the Vulva: A Rare Case Report - Harpreet Kaur; Sarvjeet Kaur; Naveenta Gupta; Deeksha Sharma (Perspective of Recent Advances in Medical Research Vol. 1, 2022)
We present a rare case of 26 years old female who presented to the emergency with frequent urination and mass in perineum. Aggressive angiomyxoma is a rare, locally invasive mesenchymal tumor occurring usually in women of reproductive age, which carries a high risk for local relapse; hence the need to differentiate it from the other mesenchymal tumors occurring in the region. Aggressive angiomyxoma is a rare condition that can look like a bartholin’s cyst. Because of its aggressive nature, it infiltrates locally, which must also be determined radiologically.